2021
DOI: 10.3389/fmed.2021.699427
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Ketogenic Diet Is Associated With Improvements in Chronic Obstructive Pulmonary Disease

Abstract: Chronic Obstructive Pulmonary Disease (COPD) is a debilitating inflammatory respiratory condition that presents with worsening breathing difficulties and it is assumed to be progressive and incurable. As an inflammatory disease, COPD is associated with recruitment of immune cells to lung tissue and increased levels of pro-inflammatory cytokines, including TNF-α, IL-1β, IL-6, IL-8, and GM-CSF. Low-carbohydrate ketogenic diets have anti-inflammatory properties that could, in theory, improve COPD symptoms and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…IL-6 is detectable in brain lesions (103) and in the CSF from people with MS (104) and plays critical roles in MS and EAE pathophysiology that include compromising blood-brain barrier integrity in combination with IL-17A (105), cooperating with transforming growth factor-b to drive the differentiation and expansion of auto-reactive TH17 cells (106)(107)(108)(109), and damaging myelin (102). Reduced circulating IL-6 by a KD has been reported (e.g., (110)(111)(112)(113)(114)(115)(116)) although studies in select populations (e.g., (117,118) and some mouse models have also reported that a KD may not change or may even increase levels of this cytokine (e.g., (119)). Reduced levels of IL-6 in the serum of KD-fed EAE mice are consistent with this dietary approach blunting CNS disease burden and maintaining motor and visual functions.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is detectable in brain lesions (103) and in the CSF from people with MS (104) and plays critical roles in MS and EAE pathophysiology that include compromising blood-brain barrier integrity in combination with IL-17A (105), cooperating with transforming growth factor-b to drive the differentiation and expansion of auto-reactive TH17 cells (106)(107)(108)(109), and damaging myelin (102). Reduced circulating IL-6 by a KD has been reported (e.g., (110)(111)(112)(113)(114)(115)(116)) although studies in select populations (e.g., (117,118) and some mouse models have also reported that a KD may not change or may even increase levels of this cytokine (e.g., (119)). Reduced levels of IL-6 in the serum of KD-fed EAE mice are consistent with this dietary approach blunting CNS disease burden and maintaining motor and visual functions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite other dietary interventions can also reduce systemic inflammation, a more relevant effect was observed in patients treated with VLCKD, thus suggesting an additional weight loss-independent anti-inflammatory effect, probably induced by ketone bodies production [59,61,62]. Considering the role of inflammation and of the innate immune system in the development of lung diseases during obesity [63,64], it is not surprising that ketogenic diet can improve OSAS [45], COPD [65], and asthma [44]. The rapid and significant loss of adiposity, which occurs mainly at the abdominal visceral compartments as previously described, reduces the mechanical obstruction of the lung that occurs in patients with android obesity.…”
Section: The Biochemical Mechanisms Of Vlckdmentioning
confidence: 99%